2020
DOI: 10.1186/s12879-020-4822-5
|View full text |Cite
|
Sign up to set email alerts
|

Comorbidities associated with HPV infection among people living with HIV-1 in the southeastern US: a retrospective clinical cohort study

Abstract: Background: The southeastern US is an epicenter for incident HIV in the US with high prevalence of human papillomavirus (HPV) co-infections. However, epidemiologies of HPV-associated clinical conditions (CC) among people living with HIV-1 infection (PLWH) are not fully known. Methods: Electronic medical records (EMR) of PLWH attending one of the leading HIV clinics in the southeastern US between 2006 and 2018 were reviewed and analyzed. The retrospective study was nested within the University of Alabama at Bir… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 15 publications
(15 citation statements)
references
References 22 publications
0
15
0
Order By: Relevance
“…Our study describes the relevant sociodemographic and clinical characteristics of PLWH diagnosed with anal HSIL and cancer in an urban HIV clinical in the Southeastern U.S. The overall incidence rates of HSIL in our clinical cohort were 338 and 194 per 100,000 person-years among men and women, respectively, with a rate of 258 AC cases per 100,000 men-years (no women presented with AC in the study) during the 12-year follow-up [ 18 ]. By contrast, data from SEER suggest that the incidence of AC in the general US population is 1.6 cases per 100,000 person-years in men and 2.2 cases per 100,000 person-years in women [ 14 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Our study describes the relevant sociodemographic and clinical characteristics of PLWH diagnosed with anal HSIL and cancer in an urban HIV clinical in the Southeastern U.S. The overall incidence rates of HSIL in our clinical cohort were 338 and 194 per 100,000 person-years among men and women, respectively, with a rate of 258 AC cases per 100,000 men-years (no women presented with AC in the study) during the 12-year follow-up [ 18 ]. By contrast, data from SEER suggest that the incidence of AC in the general US population is 1.6 cases per 100,000 person-years in men and 2.2 cases per 100,000 person-years in women [ 14 ].…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies among women living with HIV in US have reported the prevalence of anal HSIL to be 27% [ 19 ]. Our previous findings indicated that HIV-infected men had 7.9 times higher risk of incident anal HSIL (432 per 100,000 person-years), compared with HIV-infected women (55 per 100,000 person-years) [ 18 ]. Of note, during this study period, 17 out of 79 patients (21.5%) regressed to low grade squamous cell lesions (LSIL).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Detailed methods of the Joinpoint regression model were described in a previous study using the same cohort. 21 nadir, median and trajectory CD4 count analysis…”
Section: Trend Analysismentioning
confidence: 99%
“…Potential fluctuations in rates over the 18-year follow-up period was assessed by comparing rates among four time intervals (4.5 years each) in two major racial groups (AA and EA). The Joinpoint Trend Analysis software was used to detect possible trends, as described elsewhere (17,18).…”
Section: Secondary Analysis and Sensitivity Analysismentioning
confidence: 99%